ANALYSIS OF INTRINSIC AND EXTERNAL FACTORS INFLUENCING TRADERS' DECISION TO CHOOSE ISLAMIC FINANCIAL INSTITUTIONS - Yefri Joni; Iiz Izmuddin; Rahmat; Zuwardi; Al-Amin (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2025)
The purpose of this study is to find out how the Analysis of Intrinsic and External Factors that Affect Traders' Decision to Choose Islamic Financial Institutions. The method of this research is This research is a type of literature research; This means that the information materials used come from library sources in the form of books, encyclopedias, magazines, journals, newspapers, journals, and others. The form of this research is descriptive, analytical, critical and In this study, the author optimally uses two data sources related to this research, namely. Primary data sources and secondary data sources. The main source of this research is scientific books and journals The results of this research are By considering these factors, traders will make decisions that are more in accordance with their own values, needs, and conditions in choosing an Islamic financial institution.